Revisão taxonômica das espécies do gênero Centropomus Lacépède, 1802 (Perciformes, Centropomidae) do Atlântico Ocidental - Figueiredo Filho, Jessé Miranda de (2019)
The genus Centropomus Lacépède, 1802 is composed by 12 especies, generally called as snooks. These fish inhabit tropical and subtropical waters, and can be found in ocean, estuary, river and mangrove environments. Species of this genus are distributed in the Western Atlantic and Eastern Pacific. The six species of Centropomus which occur in the Western Atlantic are: Centropomus undecimalis (Bloch, 1792); C. poeyi Chávez, 1961; C. parallelus Poey, 1860; C. mexicanus Bocourt, 1868; C. pectinatus Poey, 1860; C. ensiferus Poey, 1860. The aim of this work is to review the taxonomy of species of the genus Centropomus distributed along the Western Atlantic, enlight species identity, redefine their diagnosis, descriptions, and geographic distribution. I examined 336 specimens housed in eight different scientific collections. The study was based on external morphology characters, linear and geometric morphometrics. 48 characters were used for external morphology, which 13 are discrete, 3 of spatial arrangement and 32 are linear measures. The shape and size of the body were analyzed through bidimensional geometric morphometry of 185 specimens in lateral view. Based on combination patterns of characters and analyzed measures, six species are recognized as valid taxa of the genus Centropomus in the Western Atlantic: C. undecimalis, C. sp., C. parallelus, C. ensiferus, C. pectinatus e C. poeyi. The name C. mexicanus is treated as synonymy of C. parallelus, and a new species, endemic from the North of Brazil, is recognized and described for the first time. Information on type material, diagnosis, distribution, and taxonomic comments for each taxon are provided. A taxonomic key for each species of the genus Centropomus in the Western Atlantic is provided.